Pengaruh Kepuasan Kerja dan Komitmen Organisasi Terhadap Produktivitas Kerja Karyawan di Koperasi Semarak Dana Mojokerto - Mardlyah, Nur Mirsanda Putri; Baidlowi, Imam; Poernomo, Agoes Hadi (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of job satisfaction and organizational commitment on employee productivity at the Semarak Dana Mojokerto Savings and Loan Cooperative. The problem of low discipline and performance of marketing staff is an important background, given the limited empirical studies on human resource factors in micro cooperatives in Indonesia. This study uses a quantitative approach with a total sampling technique on 35 respondents. The instrument, in the form of a questionnaire, consisted of 28 statement items measured on a 1–5 Likert scale, with validity and reliability tests showing good results (Cronbach’s Alpha > 0.70). Multiple linear regression analysis was used with the help of SPSS 26. The results of the study show that job satisfaction has a significant positive effect on productivity (β = 0.723, p < 0.05), as does organizational commitment (β = 0.555, p < 0.05). Simultaneously, these two variables contribute to an increase in employee productivity with a coefficient of determination of 77.8%. These findings support the theories of Locke (1976) and Meyer & Allen (1991) and are in line with previous studies, although the context of micro cooperatives provides unique characteristics. The practical implications of this study encourage cooperatives to strengthen their reward systems, provide training, and improve work SOPs, particularly in marketing services. The limitations of this study lie in the small sample size and cross-sectional design. Future research is recommended to use a larger sample, a longitudinal approach, and include moderator variables such as work motivation or organizational culture.